Quantifying uncertainty in time perception: A modified reproduction method - Jaume Boned; Joan López-Moliner (i-Perception)
In time perception research, we typically measure how an observer perceives time intervals by collecting data from multiple trials with a single estimate recorded on each. However, this gives us limited information about the observer's uncertainty for each estimate, which we usually measure from the variability across trials. Our study tested the potential of a modified reproduction task to provide a duration estimate as well as a measure of uncertainty on a single-trial basis. Participants were instructed to press and hold a key to temporally bracket the end of a learned duration (0.6–4 s) as narrowly as possible. Therefore, we expected the bracket's length to indicate the level of uncertainty. We compared this method to a conventional reproduction task. Taking the mid-point of the bracket as the duration estimate, we found that both methods produced equivalent data. Critically, the bracket length predicted reproduction variability, indicating that a single bracket obtained in an individual trial could potentially provide as much information as multiple reproductions. Additionally, relative variability in bracket start and end positions suggests a combination of additive and multiplicative noise components. Our findings highlight the bracket method as a more efficient and nuanced approach to measure time estimates and their associated uncertainty, expanding the methodological toolkit and opening new avenues in time perception research.